Effectiveness of Butterfly Pea ( Clitoria Ternatea ) Extract Against Streptococcus Mutans Bacterial Growth In Vitro - Siti Salmiah; Jesica Dwiasta Octaria Mp Nainggolan (Eduvest - Journal of Universal Studies, 2024)
Dental caries is still a major problem in dentistry and is the most common infectious disease in children. Caries is a microbiological infectious disease that can damage the hard tissue of the teeth. This study aims to determine the effectiveness of butterfly pea flower extract ( Clitoria ternatea ) on the growth of Streptococcus mutans in vitro. This type of research is laboratory experimental research using a post test only control group design approach The samples used were butterfly pea flower extract ( Clitoria ternatea ) diluted with DMSO to a concentration of 100%, 50%, 25%, 12.5%, 3.125%, 6.125% and Streptococcus mutans ATCC 25175. This research was conducted using the MIC test dilution method and KBM to see the effectiveness of the antibacterial extract against the test bacteria. Analysis of research data using the one way ANOVA test (p <0.05) to see significant differences between study groups with the number of test bacteria, followed by a double comparison test with the Post Hoc Least Significance Different (LSD) method to determine the average difference between treatment groups. Antibacterial effectiveness test results showed that butterfly pea flower extract ( Clitoria ternatea ) was effective in inhibiting Streptococcus mutans bacteria (p<0.05), at a concentration of 25% was the minimum inhibitory level (MIC) and 50% concentration was the minimum killing rate (MBC). ). The conclusion of this study is that the extract of butterfly pea flower ( Clitoria ternatea ) is effective in inhibiting and killing Streptococcus mutans bacteria.